Yeast carboxymethyl-glucan improves endothelial function and inhibits platelet aggregation in spontaneously hypertensive rats. Issue 9 (27th April 2022) - Bezerra, Lorena Soares; Magnani, Marciane; Pimentel, Tatiana Colombo; de Oliveira, Júlio César Pinheiro Lúcio; Freire, Francisca Manuela de Souza; de Almeida, Arthur José Pontes Oliveira; Rezende, Mathania Silva de Almeida; Gonçalves, Islânia Giselia Albuquerque; de Medeiros, Isac Almeida; Veras, Robson Cavalcante
Abstract : Carboxymethyl-glucan is a semi-synthetic derivative of β-d -glucan, a polysaccharide widely found in several natural sources, such as yeast, fungi, and cereals. Abstract : Carboxymethyl-glucan is a semi-synthetic derivative of β-d -glucan, a polysaccharide widely found in several natural sources, such as yeast, fungi, and cereals. This compound has beneficial effects on health and is considered an important immunomodulator. However, studies exploring carboxymethyl-glucan bioactivity in cardiovascular health remain lacking, mainly in hypertension. Thus, this study sought to expand understanding of the effects of carboxymethyl-glucan on vascular and platelet functions in a hypertensive animal model. Spontaneously hypertensive rats and their normotensive Wistar-Kyoto controls were assigned to five groups: control, carboxymethyl-glucan (60 mg kg −1 ), control spontaneously hypertensive rats, spontaneously hypertensive rats carboxymethyl-glucan (20 mg kg −1 ), and spontaneously hypertensive rats carboxymethyl-glucan (60 mg kg −1 ). Animals were treated for four weeks with carboxymethyl-glucan at doses of 20 and 60 mg kg −1 orally, and control rats received saline as a placebo. Vascular reactivity, platelet aggregation, and reactive oxygen species production were evaluated at the end of treatment. The results showed that carboxymethyl-glucan improved vascular function and reduced platelet aggregation, mainly at a 60 mg kg −1 dose. However, despite these effects, there was no reduction in levels of reactive oxygen species. These findings suggested that carboxymethyl-glucan modulates endothelial function. It also acts as a platelet antiaggregant, which is an interesting resource for managing hypertension and its thrombotic complications.